''REIGNING IS A DANGEROUS THING TO THE KING AND ALL OF HIS PEOPLE: THE LION KING, RENARD THE FOX AND THE MANIFESTATIONS OF POWER IN THE BOOK OF THE BEASTS - Santos, Crislayne Fatima dos [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2019)
In this paper, we will write some considerations about the multiple facets of power in Ramon Llull's work The Book of the Beasts (1232-1316). To unnoticed eyes, it may be an unpretentious story about a society of beasts who wish to elect a king. These inattentive eyes barely know that Llull illustrates the political scene of his time through a very particular animalistic perspective, fruit of his unique figure. Among the twenty-two animals that compose it, we selected two for this analysis, the Lion King and Renard the Fox and, walking among these characters, we show the multifaceted nature of the power that emerges from the carnivorous nature of the Lion to the discursive practices of the Fox. Through its lines, a society which is corrupted by power and its excesses claims for a reformation in its pillars is revealed to the reader. These are the facets that we will address in this paper.
Keywords: Power; Ramon Llull; animalistic; The Book of the Beasts